(untitled) (Economics and region, 2022)
The economic evaluation of the work in progress is the basis for the evaluation of the construction management. The planned course of management is designed on the basis of the actual determination of the initial state of object management and the expected forecast of its state in the future. The purpose of the study is to evaluate the method of measuring the quality of management as a simulation of the function of calendar planning and management on the example of the calendar schedule "Management of reconstruction of an immovable object of the historical building of the city of Odessa". The research was carried out by the method of modelling the function of calendar planning and management (a model of the management process – a calendar schedule) with the help of the assessment of the timeliness of works. It is proposed to create in the city of Odessa the "Corporate scientific and technical complex town-planning power reconstruction "CSTC T-PPR", as an innovative organisational structure, which will use in practice the accumulated scientific and technical potential for reconstruction of buildings of the historical development of Odessa according to energy efficiency standards with the involvement of foreign experience. Any general process of management of immovable property of a historical monument consists of individual management of interdependent processes: organisational, labour, information and others. A generally accepted way of their dynamic representation is a calendar plan. As the calendar plan systematically combines the economy, organisation and technology of construction production and shows the execution of works in time, it is a dynamically regulated structure. The procedure described for measuring the quality of management allows the index of the quality of management to be calculated dynamically, taking into account iteration. Moreover, this index can be used to determine the degree of responsibility of the managers of specific works. The presented model of assessing the quality of management is adequate because it is based on the modern concept of assessing the effectiveness of investment projects. In principle, this model is adaptable. However, it is necessary to take into account the dependence of the discount rate on time in order to obtain an optimal effect. Finally, the model is effective because it allows to dynamically evaluate the result of management activities and to make fairly detailed forecasts of the development of the management process.